KOMPARASI PENGELOLAAN KEUANGAN EMPAT DESA DI KABUPATEN NGANJUK - Suwandi Suwandi; Dhani Ichsanudin; Indrawati Yuhertiana (Journal of Economics Development Issues, 2019)
This study aims to analyze the results of the implementation of village financial management in terms of the effectiveness of the allocation of activities and efficiency of the budget amount of income and expenditure of villages in Nganjuk regency, with a sample of four villages, scattered and characterized by diverse topography. Qualitative research with direct observation in villages A, B, C and D, with data analysis on document of accountability report of realization of implementation of revenues and expenditure budget of village in 2015 along with the completeness document. The results showed that the village financial management can be applied well with the allocation of activities and the budget amount of village financial management is determined through village meetings in the application obtained the type of allocation of activities and the absorption of the budget size is not too big difference.